The crime of incitement to spread coronavirus infection - Abu Khamra, Dr. Youssef (The college of law and political science journal, 2023)
Since the beginning of the first societies, diseases and epidemics appear from time to time, and many of their victims fall very quickly, and this spread always causes terror among citizens and stops their working life. Therefore, states always try to avoid these epidemics and develop appropriate solutions for the conduct of public life.Despite the seriousness of the Corona virus, some may appear who underestimate the disease and invite others to mix and not adhere to prevention and health instructions, and this behavior constitutes a crime of incitement to spread the infection of the Corona pandemic, if it is responded to.The subject is of great importance as it is directly related to people’s lives, as it is a vital subject. Despite this, many citizens are ignorant of the punitive texts related to the subject of incitement to spread infection and epidemics. This may be due to the absence of a special law to regulate the provisions of this subject, despite the inclusion of some texts in the Iraqi Penal Code. In addition to the Public Health Law, it was necessary to research the regulation of this subject in addition to the need to determine the appropriate penalty.The legislator has criminalized every intentional act that may spread a dangerous disease that harms the lives of individuals, so this crime is a serious crime, as it does not necessitate the occurrence of harm, rather his act is likely to cause harm. If the damage occurred and that act resulted without the intent of death or permanent disability, the offender shall be punished with the penalty prescribed for the crime of beating leading to death or the crime of permanent disability, as the case may be, provided that the act does not intend death or harm, because in this case the provisions of premeditated murder or intentional harm apply according to the circumstances. Adverbs.Similarly, the crime of accidentally causing the spread of a dangerous disease is stipulated in Article 369 of the Penal Code, and here the legislator requires the occurrence of the consequence represented in the spread of the disease.